Burnout in the Primary Caregivers of Children With Chronic Conditions and its Related Factors - Bahareh Ahmadi; Mahdieh Sabery; Mohsen Adib-Hajbaghery (Iran University of Medical Sciences, 2021)
Background: A majority of parents of children with chronic illness encounter physical conditions, as well as some degrees of burnout, anxiety, and depression. This study examined the prevalence of burnout in the primary caregivers of children with chronic conditions and its related factors. Methods: A descriptive cross-sectional study was conducted on 385 family caregivers of children with chronic conditions who were selected by convenience sampling method from 4 healthcare centers in Kashan and Isfahan Provinces, Iran. A demographics questionnaire and the Maslach Burnout Inventory (MBI) were used to gather the required data. The MBI assesses caregiver burnout in 3 domains of emotional exhaustion, depersonalization, and reduced personal accomplishment. The obtained data were analyzed in SPSS using Mann-Whitney U test, Kruskal-Wallis test, Chi-Squared test, Fisher's Exact test, Analysis of Variance (ANOVA), and linear regression analysis. P<0.05 was considered significant. Results: The Mean±SD age of the examined caregivers and children were 38.2±8.04 and 8.9±4.9 years, respectively. Fifty percent of the research participants were fathers, and 74.3% had a family size of >4 members. The ill children were mostly boys (60%) and afflicted with renal (45.2%) or neurological (18.2%) disorders. The mean scores of the caregivers in the 3 subscales of emotional exhaustion, depersonalization, and personal accomplishment, were 22.21, 6.40, and 13.24, respectively. However, 62.3% and 47.9% of the caregivers experienced high or moderate levels of emotional exhaustion and depersonalization; nearly all of them (99.2%) experienced reduced personal accomplishment. The age of the child, the type of chronic condition, the frequency of medical visits, as well as the caregiver's age, job, income, and family size, could predict caregiver burnout (r2=0.17). Conclusion: The family caregivers of children with chronic conditions experience moderate burnout. Nurses and other healthcare providers should be aware of the signs of caregiver burnout and its contributing factors; accordingly; appropriate plans should be made for the periodic evaluation of family caregivers.